Discussion on Landscape Ecological Restoration Measures - A Case Study of Abandoned Mines - Wu, Danni (International Journal of Natural Resources and Environmental Studies, 2024)
Abandoned mines have caused many landscape ecological problems to urban development, This paper analyses the causes of the problems from the concepts related to mineral resources and mine wasteland, and briefly describes the concepts related to ecological restoration, combining with two cases of mine restoration, discusses the effective measures for the restoration of abandoned mines, which are mainly as follows: the management measures for slopes; the tailings management measures; the soil grassroots improvement; phytoremediation of heavy metal pollution in mines; restoration of water resources in mines and microbiological restoration measures.